Network pharmacology-based approach to research the effects and mechanisms of Salvia Miltiorrhiza injection against idiopathic pulmonary fibrosis - Chen, Liangyu; Lin, Haobo; Qin, Linmang; Zhang, Guangfeng; Chen, Peisheng; Jiang, Zebo; Xu, Pan; Huang, Donghui; Zhang, Xiao (Frontiers in Medicine, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a progressive, life-threatening lung disease with limited treatment efficacy. Salvia miltiorrhiza (SM), a traditional Chinese medicine (TCM), is widely used in Chinese hospitals due to its antithrombotic, anti-inflammatory, and antioxidant properties. SM has also demonstrated potential as an anti-fibrotic agent. This study aims to investigate the therapeutic effects and mechanisms of SM injection in treating IPF.MethodsActive components and targets of SM were acquired from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database, while IPF-associated genes were obtained from the DisGeNET database. Venn analysis was applied to intersect SM targets with IPF-associated genes, identifying potential therapeutic targets. A protein–protein interaction (PPI) network of these targets was constructed using the STRING database and visualized with Cytoscape software, where the CytoHubba plug-in was utilized to determine core therapeutic targets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses of the core targets were conducted via R language, and molecular docking was performed to predict the binding affinities of active compounds to the core targets. The core targets were further validated through qRT-PCR, Western blot (WB), and ELISA experiments.Results70 potential target genes of SM injection for the treatment of IPF were identified, with MMP9, IL-6, and TNF-α as the core targets. These core targets were linked to pathways involving inflammation, oxidative stress, and extracellular matrix (ECM) remodeling. In vitro experiments indicated that SM injection alleviated pulmonary fibrosis by downregulating MMP9, IL-6, and TNF-α.ConclusionSM injection may effectively reduce pulmonary fibrosis through multi-target mechanisms, providing a new therapeutic strategy for IPF from the perspective of TCM.